Antidepressant-Like Effect of Geniposide in Mice Exposed to a Chronic Mild Stress Involves the microRNA-298-5p-Mediated Nox1 - Zou, Tianyu; Zhang, Jielin; Liu, Yongxiu; Zhang, Yiming; Sugimoto, Kazuo; Mei, Cheng (Frontiers in Molecular Neuroscience, 2021)
Depression is a common mental disorder that represents a considerable challenge for public health. The natural product geniposide has neuroprotective effects on depression, but the underlying mechanism behind these effects remained undefined. The present study was designed to investigate the role of microRNAs (miRs) in this mechanism. Thus, the mouse models with depression-like behavior were established by exposure for two months to chronic unpredictable mild stress (CUMS). Then, the CUMS mice were intragastrically fed with geniposide at a dose of 10 mL/kg daily for two consecutive weeks. We monitored the depression-like behaviors of CUMS mice by the forced swimming test (FST) and tail suspension test (TST). Then, we measured the cerebral expression of miR-298-5p and NADPH oxidase 1 (Nox1) mRNA in CUMS mice by the RT-qPCR. The targeting relationship between miR-298-5p and Nox1 was evaluated by dual-luciferase reporter gene assay. The concentrations of adenosine triphosphate (ATP) and reactive oxygen species (ROS) were determined by the CellTiter-Glo® and flow cytometry, respectively. The mitochondrial membrane potential (MMP) was detected using JC-1 staining. Moreover, the expression of inflammatory cytokines (TNF-α, IL-1β, IL-6, and TGF-β) was determined by ELISA, RT-qPCR, and western blot analysis. We found that miR-298-5p was poorly-expressed while Nox1 was highly-expressed in brain tissues of CUMS-induced mice. Intriguingly, Geniposide treatment reversed the behavioral abnormalities of CUMS mice, including shortened immobility time. Geniposide inhibited the Nox1 expression by increasing miR-298-5p levels. There were increased ATP content and MMP and reduced contents of ROS and inflammatory cytokines in CUMS mice receiving geniposide treatment. Hence, this study revealed an antidepressant effect of geniposide on CUMS-induced depression-like behavior in mice by down-regulating the miR-298-5p-targeted Nox1. This highlights a novel candidate target for the treatment of depression.